A seed flying like a bullet: ballistic seed dispersal in Chinese witch-hazel (Hamamelis mollis OLIV., Hamamelidaceae). Issue 157 (30th August 2019) - Poppinga, Simon; Böse, Anne-Sophie; Seidel, Robin; Hesse, Linnea; Leupold, Jochen; Caliaro, Sandra; Speck, Thomas
Abstract : The fruits of Chinese witch-hazel ( Hamamelis mollis, Hamamelidaceae) act as 'drying squeeze catapults', shooting their seeds several metres away. During desiccation, the exocarp shrinks and splits open, and subsequent endocarp deformation is a complex three-dimensional shape change, including formation of dehiscence lines, opening of the apical part and formation of a constriction at the middle part. Owing to the constriction forming, mechanical pressure is increasingly applied on the seed until ejection. We describe a structural latch system consisting of connective cellular structures between endocarp and seed, which break with a distinct cracking sound upon ejection. A maximum seed velocity of 12.3 m s −1, maximum launch acceleration of 19 853 m s −2 (approx. 2000 g ) and maximum seed rotational velocity of 25 714 min −1 were measured. We argue that miniscule morphological differences between the inner endocarp surface and seed, which features a notable ridge, are responsible for putting spin on the seed. This hypothesis is further corroborated by the observation that there is no preferential seed rotation direction among fruits. Our findings show that H. mollis has evolved similar mechanisms for stabilizing a 'shot out' seed as humans use for stabilizing rifle bullets and are discussed in an ecological (dispersal biology), biomechanical (seed ballistics) and functional–morphological (fine-tuning and morphospace of functional endocarps) contexts, and promising additional aspects for future studies are proposed.